2011
DOI: 10.1007/s00167-011-1791-7
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of intraarticular morphine–bupivacaine and tramadol–bupivacaine in postoperative analgesia after arthroscopic anterior cruciate ligament reconstruction

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…This result was consistent with some previous research. 5,31,34,37,38 Nevertheless, we have to recognize the fact that none of the included studies included a long enough observation to detect the chondrotoxics of IA bupivacaine or morphine. Park et al 39 suggested that IA bupivacaine should be used cautiously for its detrimental chondrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with some previous research. 5,31,34,37,38 Nevertheless, we have to recognize the fact that none of the included studies included a long enough observation to detect the chondrotoxics of IA bupivacaine or morphine. Park et al 39 suggested that IA bupivacaine should be used cautiously for its detrimental chondrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, period of time when the study has been conducted was not specified in the Hosseini et al [5] article. We are curious if the authors were aware of the adverse chondrotoxic effect of bupivacaine and if it was mentioned in the application to the ethics committees in Shahid Sadoughi University of Medical Sciences.…”
Section: Chondrotoxic Effect Of Intraarticular Bupivacaine Administramentioning
confidence: 99%
“…1,2 Nonsteroidal anti-inflammatory drugs (NSAIDs) are frequently used for controlling arthroscopic pain 1,2 and have been administered alone or as intraarticular combinations with local anesthetics or opioids for these procedures. 2,3 This group of drugs have been demonstrated to reduce pain and inflammation due to arthroscopy, as well as effusions related to inflammation, by inhibiting prostaglandin synthesis. 4 The preoperative administration of NSAIDs may be more effective in reducing postoperative pain by inhibiting prostanoid production before the development of tissue injury.…”
Section: Introductionmentioning
confidence: 99%